Migration Impact Of Risk Management Functions On The Enterprise Risk Management In The UAE - Alkaabi, Mohamed Matar Saleh Sulaiman; Hussain, Tuan Pah Rokiah binti Syed; Romle, Abd Rahim (Migration Letters, 2024)
Background: The critical role of effective risk management functions within organizations has garnered significant attention, particularly within public sector entities where the implications of risk have broad societal impacts. The United Arab Emirates (UAE) Ministry of Interior represents a pivotal institution where the integration of comprehensive risk management strategies is paramount to national security and operational efficiency. Objective: This research aims to explore the direct impact of risk management functions namely risk identification, risk assessment, risk response, and risk monitoring and reporting on enterprise risk management (ERM) within the UAE Ministry of Interior. By grounding the investigation in risk management theory, the study seeks to validate a conceptual framework that posits these four functions as critical determinants of ERM efficacy. Method: Utilizing a quantitative research methodology, the study evaluates the proposed hypotheses through statistical analysis of primary data collected from 358 full-time employees in leadership positions at the UAE Ministry of Interior. This approach allows for a rigorous examination of the relationship between the risk management functions and ERM effectiveness. Results & Conclusion: The findings underscore a significant influence of the risk management functions on enterprise risk management within the UAE Ministry of Interior, affirming the hypothesized relationships within the proposed conceptual framework. Each function of risk management identification, assessment, response, and monitoring and reporting demonstrated a statistically significant impact on ERM, highlighting the importance of these activities in enhancing organizational risk management capabilities. In light of these findings, the research advocates for further comparative studies between the public and private sectors to deepen the understanding of ERM practices. Additionally, it suggests the exploration of other variables that may influence ERM and the examination of potential moderating factors. This study contributes to the body of knowledge by providing empirical evidence on the [1]significance of risk management functions in public sector organizations, specifically within the context of the UAE Ministry of Interior, and sets a foundation for future research in this vital area.